THE APPLICATIONS GROUPER SEED PRODUCTION TECHNOLOGY TO SUPPORT MARICULTURE DEVELOPMENT - Suko Ismi (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2014)
Application technology for grouper seed production was conducted by dissemination activities, aimed for dissemination technology in several places having aquaculture prospects in order to facilitate seed supply. The research was conducted in 2012 collaborated with the Department of Fisheries and Maritime Affairs Lamongan Regency and Fisheries Academy of Sidoarjo. Application technology for grouper seed production was conducted in Tunggu village, Paciran district, Lamongan, East Java. Grouper seeds which maintained were tiger, cantik, and cantang. Seed productions were performed from egg to juvenile with size of ±3.0 cm,in which the eggs were transported from hatchery in Bali and larval rearing was conducted based on the produced technology. The results showed that survival rate of tiger grouper was 8.3%, cantang grouper was 11,6%, and cantik grouper was 12.4%. The results showed that R/C ratio was >1, in which the business was profitable. The technology can be applied to the community and grouper seed production can support aquaculture activities. Keywords: Grouper seed, production, technology, R/C ratio, aquaculture